Peran Intellectual Capital Dalam Kinerja Keuangan Syariah - Abdul Nasser Hasibuan; Windari Windari (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2023)
The results of this study aim to determine the Role of Intellectual Capital in Islamic Financial Performance. Simple research method The data source used is secondary data taken from the sites www.ojk.co.id and www.bankbrisyariah.co.id and www.bankbtpn syariah.co. identifier. The samples used were 48 samples. The analysis technique used was descriptive test, normality test, panel data analysis method, hypothesis testing namely t test, determination test (R2), and simple regression, then the data were analyzed using version 9 review. Based on the results of partial hypothesis testing (t test ) shows that iB-VAIC has a positive effect on Return On Assets with the level of influence tcount ttable, while the test of the coefficient of determination (R2) shows iB-VAIC has a positive effect on Return On Assets with an influence level of 82.55%. 45% is explained by other variables not discussed in this study.